2014
DOI: 10.1007/s13191-014-0355-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resin Cement Mixing Method on the Retention Strength of a CAD/CAM Zirconia Crowns

Abstract: Several treatments have been suggested to improve the retention of zirconia-based restorations luted with different cements. Resin cements are believed to improve crown retention under certain circumstances. The aim of the present study was to examine the effect of three cements with different mixing methods on the retention of CAD/CAM zirconia crowns. Thirty extracted human molars were randomly divided into three groups and prepared for all-ceramic crowns (6° taper, 4-mm height and a 1.2 mm rounded shoulder f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…On the other hand, restorations in Zr group did not bene t from the adhesive bond of resin cement as much as restorations in ZLS group did. Sadighpour et al showed 279.19 N ±50.14 retention force in zirconia crowns sandblasted with aluminum oxide particles and cemented with Panavia F2.0 dual cure resin cement which is approximately similar to the retention force in Zr group in the present study (271.50 N ±114.31) [34].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, restorations in Zr group did not bene t from the adhesive bond of resin cement as much as restorations in ZLS group did. Sadighpour et al showed 279.19 N ±50.14 retention force in zirconia crowns sandblasted with aluminum oxide particles and cemented with Panavia F2.0 dual cure resin cement which is approximately similar to the retention force in Zr group in the present study (271.50 N ±114.31) [34].…”
Section: Discussionsupporting
confidence: 84%
“…2). The failure modes were classi ed as type 1 for cohesive failure of cement layer, type 2 for adhesive failure at the cement-tooth interface, type 3 for adhesive failure at the cement-restoration interface, and type 4 for mixed failures [34].…”
Section: Methodsmentioning
confidence: 99%
“…3 ). Failure modes were classified as type 1 for cohesive failure of cement layer, type 2 for adhesive failure at the cement-tooth interface, type 3 for adhesive failure at the cement-restoration interface, and type 4 for mixed failures [ 41 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…[ 8 ] Whereas, the glass-free polycrystalline microstructure of zirconia ceramics does not allow such reaction. [ 9 ] Resin cement–zirconia bond can be improved through various methods such as the micromechanical means of airborne-particle abrasion[ 10 11 12 ] or chemical activation with specific monomers such as 10-methacryloyloxydecyl dihydrogen phosphate (MDP) and 4-methacryloxy ethyl trimellitic anhydride. [ 13 14 15 16 17 ]…”
Section: Introductionmentioning
confidence: 99%